Tilakamañjarī, eka samīkshātmaka adhyayana - Dīkshita, Harinārāyaṇa, 1936- (Bhāratīya Vidyā Prakāśana, 1982)
Study of Dhanapāla's Tilakamañjarī, 10th century Sanskrit poem in mixed prose and verse (campū)